The Laboratory Diagnosis of Bacterial Vaginosis - Deborah Money (Canadian Journal of Infectious Diseases and Medical Microbiology)
Bacterial vaginosis (BV) is an extremely common health problem for women. In addition to the troublesome symptoms often associated with a disruption in the balance of vaginal flora, BV is associated with adverse gynecological and pregnancy outcomes. Although not technically a sexually transmitted infection, BV is a sexually associated condition. Diagnostic tests include real-time clinical/microbiological diagnosis, and the current gold standard, the standardized evaluation of morphotypes on Gram stain analysis. The inappropriate use of vaginal culture can be misleading. Future developments into molecular-based diagnostics will be important to further understand this complex endogenous flora disruption.